Teachers’ Strategies in Islamic Religious Education for Developing Students’ Religious Character in a Vocational School - Risma Solehah; Chepiq Aziz; Ayi Haedar Saputra; Dewi Nurhasanah; Hera Rosliana Nurdaputri (Journal of Teacher Training and Educational Research, 2025)
The integration of religious character education in vocational schools is an urgent need, as students are not only prepared for academic and professional competencies but also required to possess strong spiritual and moral foundations. This study aimed to explore the learning strategies employed by Islamic Religious Education (PAI) teachers in strengthening students’ religious character at SMK Islam Terpadu Al-Hidayah. This research applied a qualitative case study design. Data were collected through in-depth interviews with PAI teachers and students, classroom observations, and documentation analysis. The data were analyzed using Miles, Huberman, and Saldaña’s interactive model, while data credibility was ensured through triangulation and member checking. The findings revealed three main strategies applied by PAI teachers. First, role modeling, in which teachers consistently exemplified religious values through daily attitudes and behaviors. Second, habituation strategies, including structured religious routines such as congregational prayers, Qur’an recitation, and dhikr. Third, integration of religious values into learning, in which Islamic teachings were contextualized with academic subjects and vocational practices, making them relevant to students’ personal and professional lives. In conclusion, the synergy of these strategies created a holistic and practical approach to character education that effectively strengthened students’ religiosity and discipline. The study recommends that vocational schools institutionalize religious character education alongside academic and vocational training to better prepare students for both workplace competence and ethical responsibility.